Pengaruh Media Pasir Ajaib terhadap Kemampuan Motorik Halus Anak Usia 4-5 Tahun di TK Ihyaul Ulum Lamongan - Dwi Aminatus Sa'adah; Misbahul Huda; Layyinatul Mursyidah (Institut Agama Islam Nahdlatul Ulama Tuban, 2022)
Abstract: The aim of this study was to determine the effect of magic sand media on the fine motor skills of children aged 4-5 years at Kindergarten Ihyaul Ulum Lamongan. This study uses a quantitative research approach. This study used a pre-experimental design with the type of one group pre-test post-test design. The subjects in this study were group A children (age 4-5 years) at Ihyaul Ulum Lamongan Kindergarten, totaling 16 children. Data collection techniques used are observation and documentation. The data analysis technique uses the Wilcoxon Matched Pairs Test. Based on the results of data analysis obtained Tcount = 0 and T table for N = 16 Significant level of 5% is 30, then (0 <30). The data shows that Ho is rejected and Ha is accepted. The results of research on magic sand media have an effect on children's fine motor skills. This is because the activity of making various shapes is carried out in stages according to the stages of the child's fine motor development. In addition, the magic sand media is a media with synthetic ingredients which produces sand with a softer texture than beach sand, not messy and only sticks to the kinesthetic sand itself. Even though it is made of synthetic materials, this sand is safe for toys. Magic sand is very soft and malleable. The combination shape of magic sand is made of a material that is not too hard, but also not too soft, so this magic sand toy is perfect for making as a child's toy. Apart from that, magic sand media is also able to stimulate fine motor skills, has many colors, and can attract children's interest.